Implementation of Card Sort Learning Media in Islamic Education Class in MIN - Baidar, Baidar; Mutathahirin, Mutathahirin; Fitriani, Fitriani (Khalaqa: Journal of Education and Learning, 2023)
The learning method is an effort to help and make it easier for teachers to transform learning material to students. The fact at MIN 3 Padang Pariaman is that students do not understand the material well even though the teacher has applied various methods, one of which is the card sort method. So, how is the application of the card sort method by teachers at MIN 3 Padang Pariaman? Thus, the research objective to be achieved is to describe the planning, implementation, and inhibiting factors for the application of the card sort method by MIN 3 Padang Pariaman teachers. In order to find these answers, this study uses a qualitative descriptive method. Data collection techniques used by observation, interviews, and documentation of existing data sources. Thus, the results of this study indicate that there are still MIN 3 Padang Pariaman teachers who have not fully mastered the card sort technique.